ANALYSIS MODEL TYPE OF COOPERATIVE LEARNING GROUP BASED ON COLLABORATIVE INVESTIGATION AND SCIENTIFIC ATTITUDE TOWARDS STUDENT LEARNING OUTCOMES PHYSICS SMA NEGERI 1 SECANGGANG - Arko Alfathar Tumanggor; Sahyar . (Jurnal Pendidikan Fisika, 2015)
The purposes of the research are to determine the differences between learning outcomes physics students with cooperative learning model based Collaborative Group Investigation and learning model of Direct Instruction; The difference in results between the groups studied physics scientific attitude is low and the high; Interaction between learning model with the level of scientific attitude of students in influencing student learning outcomes. The sampling technique in this study conducted in cluster random sampling of two classes, where first class as a class experiment applied cooperative learning model Group Investigation and second class as a class of control applied learning model of Direct Instruction. The instruments used in this research achievement test physics in the form of descriptions of 10 questions and instrument scientific attitude questionnaire with 22 questions that have been declared valid and reliable. From the results of this study concluded that there are differences in learning outcomes physics students with cooperative learning model Group Investigation based collaborative learning and model direct instruction learning, this means that learning outcomes of students who learned with group investigation model of learning is better than learning model of direct instruction. There are differences between groups of low scientific attitude and high scientific attitude; this means that the learning outcomes of students who have high scientific attitude is better than learning outcomes of students who have low scientific attitude. There is interaction between learning models with the level of scientific attitude of students in influencing student learning outcomes; this means that the model of good cooperative group investigation applied to students who have a high scientific attitude.